Congenital linear ulcerative and scarring lesions associated with fetus papyraceus. Unilateral aplasia cutis congenita type V? - Milano, A. (European Journal of Pediatric Dermatology, 2023)
Aplasia cutis congenita (ACC) is rarely caused by obvious causes. An exception is ACC associated with fetus papyraceus, i.e. death in utero of a twin and in these cases the ACC that occurs in the surviving twin is attributed to hemodynamic disorders. An exceptional unilateral case of ACC associated with fetus papyraceus is presented.